Expression of Respiratory Syncytial Virus-Induced Chemokine Gene Networks in Lower Airway Epithelial Cells Revealed by cDNA Microarrays - Zhang, Yuhong (American Society for Microbiology, 2001)
The Paramyxovirus respiratory syncytial virus (RSV) is the primary etiologic agent of serious epidemic lower respiratory tract disease in infants, immunosuppressed patients, and the elderly. Lower tract infection with RSV is characterized by a pronounced peribronchial mononuclear infiltrate, with eosinophilic and basophilic degranulation. Because RSV replication is restricted to airway epithelial cells, where RSV replication induces potent expression of chemokines, the epithelium is postulated to be a primary initiator of pulmonary inflammation in RSV infection. The spectrum of RSV-induced chemokines expressed by alveolar epithelial cells has not been fully investigated. In this report, we profile the kinetics and patterns of chemokine expression in RSV-infected lower airway epithelial cells (A549 and SAE). In A549 cells, membrane-based cDNA macroarrays and high-density oligonucleotide probe-based microarrays identified inducible expression of CC (I-309, Exodus-1, TARC, RANTES, MCP-1, MDC, and MIP-1α and -1β), CXC (GRO-α, -β, and -γ, ENA-78, interleukin-8 [IL-8], and I-TAC), and CX(3)C (Fractalkine) chemokines. Chemokines not previously known to be expressed by RSV-infected cells were independently confirmed by multiprobe RNase protection assay, Northern blotting, and reverse transcription-PCR. High-density microarrays performed on SAE cells confirmed a similar pattern of RSV-inducible expression of CC chemokines (Exodus-1, RANTES, and MIP-1α and -1β), CXC chemokines (I-TAC, GRO-α, -β, and -γ, and IL-8), and Fractalkine. In contrast, TARC, MCP-1, and MDC were not induced, suggesting the existence of distinct genetic responses for different types of airway-derived epithelial cells. Hierarchical clustering by agglomerative nesting and principal-component analyses were performed on A549-expressed chemokines; these analyses indicated that RSV-inducible chemokines are ordered into three related expression groups. These data profile the temporal changes in expression by RSV-infected lower airway epithelial cells of chemokines, chemotactic proteins which may be responsible for the complex cellular infiltrate in virus-induced respiratory inflammation.